The Neogene Savannas of North America: A Retrospective Analysis on Artiodactyl Faunas - Morales-García, Nuria Melisa; Säilä, Laura K.; Janis, Christine M. (Frontiers in Earth Science, 2020)
Savanna-like ecosystems were present at high latitudes in North America during much of the Neogene. Present-day African savannas, like the Serengeti, have been proposed to be modern analogues of these paleosavannas, particularly those from the middle Miocene of the Great Plains region of the United States. Both these extant and extinct savannas contain a preponderance of artiodactyl (even-toed ungulate) species; however, the taxonomic composition of each fauna is different. While present-day African savannas are dominated by ruminants (primarily bovids), the Neogene savannas of North America were dominated by a diversity of both camelid and non-bovid ruminant families. This study provides a quantitative test of the similarity of the artiodactyl faunas of the North American Neogene paleosavannas to those of the modern-day African savannas. A correspondence analysis of ecomorphological features revealed considerable overlap between modern and fossil faunas. The morphospace occupation of the extinct North American ruminants falls within that of the African bovids. Some of the extinct camelids also fall within this same morphospace, but many do not, perhaps indicating an environmental difference such as greater aridity in Neogene North America. The diversity and disparity of artiodactyl faunas through the Neogene of North America changed along with changing temperatures and precipitation regimes. The taxonomic and ecomorphological diversity of the Serengeti ruminant fauna is statistically comparable to those North American paleofaunas occurring during or immediately after the Middle Miocene Climatic Optimum (MMCO), but the later, more depauperate faunas are no longer comparable. This study quantitatively analyzes artiodactyl communities as they changed with the cooling and drying trend seen during the Neogene.